Neck Location on the Outer Convexity is a Predictor of Incomplete Occlusion in Treatment with the Pipeline Embolization Device: Clinical and Angiographic Outcomes - Sunohara, T.; Imamura, H.; Goto, M.; Fukumitsu, R.; Matsumoto, S.; Fukui, N.; Oomura, Y.; Akiyama, T.; Fukuda, T.; Go, K.; Kajiura, S.; Shigeyasu, M.; et al. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: With the increasing use of the Pipeline Embolization Device for the treatment of aneurysms, predictors of clinical and angiographic outcomes are needed. This study aimed to identify predictors of incomplete occlusion at last angiographic follow-up.MATERIALS AND METHODS: In our retrospective, single-center cohort study, 105 ICA aneurysms in 89 subjects were treated with Pipeline Embolization Devices. Patients were followed per standardized protocol. Clinical and angiographic outcomes were analyzed. We introduced a new morphologic classification based on the included angle of the parent artery against the neck location: outer convexity type (included angle, <160°), inner convexity type (included angle, >200°), and lateral wall type (160° ≤ included angle ≤200°). This classification reflects the metal coverage rate and flow dynamics.RESULTS: Imaging data were acquired in 95.3% of aneurysms persistent at 6 months. Complete occlusion was achieved in 70.5%, and incomplete occlusion, in 29.5% at last follow-up. Multivariable regression analysis revealed that 60 years of age or older (OR, 5.70; P = .001), aneurysms with the branching artery from the dome (OR, 10.56; P = .002), fusiform aneurysms (OR, 10.2; P = .009), and outer convexity–type saccular aneurysms (versus inner convexity type: OR, 30.3; P < .001; versus lateral wall type: OR, 9.71; P = .001) were independently associated with a higher rate of incomplete occlusion at the last follow-up. No permanent neurologic deficits or rupture were observed in the follow-up period.CONCLUSIONS: The aneurysm neck located on the outer convexity is a new, incomplete occlusion predictor, joining older age, fusiform aneurysms, and aneurysms with the branching artery from the dome. No permanent neurologic deficits or rupture was observed in the follow-up, even with incomplete occlusion.MCRmetal coverage ratioPEDPipeline Embolization Device